2014
DOI: 10.1038/srep05199
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic equilibrium of heterogeneous and interconvertible multipotent hematopoietic cell subsets

Abstract: Populations of hematopoietic stem cells and progenitors are quite heterogeneous and consist of multiple cell subsets with distinct phenotypic and functional characteristics. Some of these subsets also appear to be interconvertible and oscillate between functionally distinct states. The multipotent hematopoietic cell line EML has emerged as a unique model to study the heterogeneity and interconvertibility of multipotent hematopoietic cells. Here we describe extensive phenotypic and functional heterogeneity of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 60 publications
(201 reference statements)
2
10
0
Order By: Relevance
“…6A). This result reveals cell plasticity in population dynamics based on the proposed model, quantitatively explain the phenomena of dynamic equilibrium in stem cell regenerations [5,26,39,68].…”
Section: Rongsheng Huang and Jinzhi Leisupporting
confidence: 61%
“…6A). This result reveals cell plasticity in population dynamics based on the proposed model, quantitatively explain the phenomena of dynamic equilibrium in stem cell regenerations [5,26,39,68].…”
Section: Rongsheng Huang and Jinzhi Leisupporting
confidence: 61%
“…In competitive transplantation assays, the reconstitution capability of Prmt5 D/D HSCs was severely compromised (Figures 1D and 1E). We confirmed the requirement for PRMT5 activity in HSCs using the multipotent, stem cell factor (SCF)-dependent murine hematopoietic cell line EML, which is recognized as an in vitro surrogate for primary HSPCs (Weston et al, 2014). Using the well-characterized PRMT5 inhibitor EPZ015666 (Chan-Penebre et al, 2015), we depleted PRMT5 activity in EML cells ( Figure 1F), which led to a corresponding decrease in EML cell proliferation and viability, particularly for concentrations R 5 mM ( Figures 1G and 1H).…”
Section: Hsc Maintenance Requires Cell-intrinsic Prmt5 Activitymentioning
confidence: 56%
“…Dynamic equilibrium of sub-states of stem cells is observed not only in the EMT system, but also in hematopoietic and embryonic stem cell populations [11] [27] [34]. Moreover, it was suggested that heterogeneity of cell population might be related to disseminated cancer cell dormancy [28].…”
Section: Discussionmentioning
confidence: 99%